Penguatan Kompetensi Metode Penelitian dan Pengabdian dalam Penyusunan Proposal bagi Para Dosen Muda di IAI Al-Qolam Gondanglegi Malang - Setiawati, Eti; Al Uyun, Dhia; Riskiyah, Faridatur; Pratiwi, Baiq (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
An advanced nation is one whose human resources are of the highest quality. The excellence of human resources can only be achieved through education, which involves educators and students, lecturers and pupils, lecturers and university students. Community service is carried out as a manifestation of expertise contribution, the utilization of educational outcomes, and/or research in the fields of science, technology, and/or art, in efforts to meet demands or initiate improvements in the quality of life of the community. Therefore, this community service aims to enhance the competence of community service proposals at the Islamic Religious Institute (IAI) Al-Qolam, commonly referred to as IAI Al-Qolam. The outcome of this community service is to provide training and mentoring, strengthen research and community service methods in proposal development for young faculty members at IAI Al-Qolam Gondanglegi Malang, so that faculty members can perform their duties more professionally and effectively.